(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
The main source cattle feed is fodder, it is essential to proper management. Furthermore, this combined with other type of grazing may or may not generate positive environmental effects. Unfortunately tropical livestock has been characterized as a production model with large tracts of land and low diversity of forage species, with the degradation of pastures and soils the main problem being faced by producers to reduce the supply of fodder, leading them to work in economically unsustainable systems, increasing the morality weight given by the change in land use over the past 50 years the deforestation of native forests (more than 77%), in order to devote the production of green fodder for mishandling end up becoming an environmental failure.